THE APPLICATION OF LOCAL WISDOM-BASED LKPD TO IMPROVE IPS LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Munjiatun Munjiatun; Zufriady Zufriady; Non Syafriafdi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study aims to improve student learning outcomes through the application of LKPD (Learner Worksheet) based on local wisdom. Indonesian local character is important to be taught to students including through teaching materials in the form of LKPD based on local wisdom that can be used as a reference in the learning process. LKPD is one of the teaching materials in which there are all the basic activities carried out by students which aim to maximise understanding and formation of basic abilities in accordance with the indicators of competency achievement. The research used is Classroom Action Research (PTK) using the research design of the Kemmis and Mc. Taggart model research design. This research was conducted at SDN 189 Pekanbaru. The research subjects were 20 fourth grade students. This research uses quantitative data analysis. Descriptive statistical data collection techniques were carried out as well as observation, interviews and evaluation tests at the end of the cycle. The results of cycle I to cycle II have increased significantly with a passing percentage of 75%, and 35% of students whose scores have not met the KKM standard, it can be seen that the learning outcomes of students in social studies learning through the application of local wisdom-based LKPD learning media have increased. The average of students increased from the initial reflection of 62.25 with the highest score of 80 and the lowest score of 35 to 74.00, with the highest score of 90 and the lowest score of 40 in cycle I although it was not in accordance with the KKM that had been determined when cycle II experienced an increase of 80.00 with the highest score of 90 and the lowest score of 55.